Numerical Study of Four Bolts End-Plate Joint Behaviour for Robustness Assessment - Saleh, Bashir (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
The paper presents new studies on numerical modeling (FEM) for beam-to-column behavior under sagging and hogging bending moment when the framework is exposed to service and unexpected loads that may cause a column loss scenario. This investigation is focused on four bolts end-plate joints with 10 mm thickness which are proven experimentally to have more ductile behavior than other end-plates joints (6, 8 bolts), spite of their weakness to transfer the unexpected loads from the initial state to a residual state of the stable equilibrium, that leads to a failure of limited floor area to adjacent joints when tested experimentally (Saleh, 2014). FEM technique used in this research is an extension of the previous technique and is characterized by the use of a more sophisticated technique than the previous, discovered from the result of continuous research and the use of all the options available in the new version of commercial ABAQUS/CAD software. The elements are designed using multiple layers of specific elements of a brick arranged in such a way that the mesh nodes of the tiles should coincide with certain layers with the top of the shear inlay and in line with reinforcement, not as the former study that used thick shell elements to model the reinforced concrete slab with total negligence of reinforcing steel and bolts between the slap and the beam. This investigation is very complex because of highly nonlinear effects associated with the prediction of joint performance, such as structural imperfections, huge displacements and large rotations, inelastic properties of steel and concrete, bonding effects between steel and concrete, friction between end-plate and column flange and focus on the slip between concrete and structural steel, among others which is the most difficult modelling application. The paper addresses all these problems in addition to an evaluation of the joint with four bolts end-plate and provides recommendations for new computer simulation techniques (FEM). With these satisfactory results, this technique can be used to solve many problems and difficulties facing the steel and steel-concrete composite frames due to extraordinary events (explosions and hurricanes).